Phylogeography and disjunct distribution in Lychnophora ericoides (Asteraceae), an endangered cerrado shrub species - Collevatti, Rosane Garcia (Oxford University Press, 2009)
BACKGROUND AND AIMS: Lychnophora ericoides (Asteraceae) presents disjunct geographical distribution in cerrado rupestre in the south-east and central Brazil. The phylogeography of the species was investigated to understand the origin of the disjunct geographical distribution. METHODS: Populations in the south and centre of Serra do Espinhaço, south-east Brazil and on ten other localities in Federal District and Goiás in central Brazil were sampled. Analyses were based on the polymorphisms at chloroplast (trnL intron and psbA-trnH intergenic spacer) and nuclear (ITS nrDNA) genomes. From 12 populations, 192 individuals were sequenced. Network analysis, AMOVA and the Mantel test were performed to understand the relationships among haplotypes and population genetic structure. To understand better the origin of disjunct distribution, demographic parameters and time to most recent common ancestor (T(MRCA)) were estimated using coalescent analyses. KEY RESULTS: A remarkable differentiation between populations from the south-east and central Brazil was found and no haplotype was shared between these two regions. No significant effect of isolation by distance was detected. Coalescent analyses showed that some populations are shrinking and others are expanding and that gene flow between populations from the south-east and central Brazil was probably negligible. CONCLUSIONS: The results strongly support that the disjunct distribution of L. ericoides may represent a climatic relict and that long-distance gene flow is unlikely. With an estimated time to most recent common ancestor (T(MRCA)) dated from approx. 790 655 ± 36 551 years bp (chloroplast) and approx. 623 555 ± 55 769 years bp (ITS), it was hypothesized that the disjunct distribution may be a consequence of an expansion of the geographical distribution favoured by the drier and colder conditions that prevailed in much of Brazil during the Kansan glaciation, followed by the retraction of the distribution due to the extinction of populations in some areas as climate became warmer and moister.